PENGARUH MODEL KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK KELAS IV DI SEKOLAH DASAR - Pilda Nurohmah; Dindin MZM; Feby Inggriyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the low speaking skills of students in elementary schools. The purpose of this study is to determine the effect of the Think Pair Share type cooperative model on the speaking skills of fourth grade students at SDN 160 Sukalaksana Bandung City in the 2023/2024 academic year. This study uses a type of quantitative research with a quasi experiment method with a research design of nonequivalent control group design. The population used in this study were all fourth grade students of SDN 160 Sukalaksana Bandung City, with a sample of two classes, namely class IV-A with 27 students as the experimental class, and class IV-B with 27 students as the control class. The data of this study were obtained using a speaking skill assessment rubric which was validated using the opinion of experts (judgment experts). The results showed that: 1) The description of the learning process of the experimental class is better than the control class, and the application of the Think Pair Share type cooperative learning model can affect students' speaking skills. 2) The results of the hypothesis test obtained sig. (2-tailed) of 0.000, which is less than 0.05 so that there is a difference in speaking skills between students who use the Think Pair Share type cooperative learning model and students who use the conventional model. 3) There is an increase in students' speaking skills between students who use the Think Pair Share type cooperative learning model and students who use conventional models, this can be seen through the average value of the experimental class pretest of 46.85, and the average post-test of 81.67. Meanwhile, the control class obtained an average pretest of 43.78, and an average post-test of 73.78. 4) Based on the effect size results, the use of the Think Pair Share type cooperative learning model has an influence of 1.18 on students' speaking skills. Based on the analysis of the data obtained, it can be concluded that using the Think Pair Share type cooperative learning model can affect the speaking skills of students in class IV SDN 160 Sukalaksana.